2000
DOI: 10.1021/bi9929709
|View full text |Cite
|
Sign up to set email alerts
|

Hydration Changes Implicated in the Remarkable Temperature-Dependent Membrane Permeation of Cyclosporin A

Abstract: Cyclosporin A is a cyclic peptide believed to exist as multiple conformers in aqueous solution. Two major conformations, distinguished by a single cis-trans isomerization and the presence of four either intramolecular or intermolecular hydrogen bonds, have been confirmed depending on whether CsA is characterized in organic solvents or bound in aqueous complex with cyclophilin. The relationship between CsA conformation and its ability to penetrate biological membranes is currently unknown. Using Caco-2 cell mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 44 publications
1
43
0
1
Order By: Relevance
“…In spite of cyclosporine A being a relatively large cyclic peptide, this drug shows high permeability across membrane and is well absorbed from the gut after oral administration. Drug conformation, including intramolecular hydrogen bonding, has been considered as a determinant in cyclosporine A's high permeability16.…”
Section: Resultsmentioning
confidence: 99%
“…In spite of cyclosporine A being a relatively large cyclic peptide, this drug shows high permeability across membrane and is well absorbed from the gut after oral administration. Drug conformation, including intramolecular hydrogen bonding, has been considered as a determinant in cyclosporine A's high permeability16.…”
Section: Resultsmentioning
confidence: 99%
“…Cyclosporine adopts a conformation where internal hydrogen bonds result in a conformation displaying a hydrophobic surface while masking polar regions to facilitate membrane transit. 575, 576 In the specific case of cyanobactins, macrocyclization also removes the zwitterionic N- and C-terminal charges. Heterocyclization further increases the hydrophobicity of the natural product.…”
Section: Cyanobactinsmentioning
confidence: 99%
“…It could be secreted together with certain extracellular proteins and it should be able to sequester some quantity of the in vivoadministered CsA. It was also shown that a modified form of CsA anchored to the surface of T cells could exert its immunomodulatory effects [100], as negatively charged CsA derivatives rest in the extracellular space [101] whereas CsA binds well to the membranes in a temperature-dependent fashion [102]. If CsA binds to the extracellular pool of hCyPB, then such a complex has two crucial attributes for entering into the cell's interior, namely the large exposed hydrophobic patch of CsA should have some affinity to the hydrophobic environment of the membranes while the positively charged patches of CyPB should induce a substantial driving force for entry into T cells.…”
Section: Extracellular Effects Of the Cyclophilinsmentioning
confidence: 99%